Uso da água, rendimento de grãos e teores de óleo de girassol submetido a diferentes estratégias de irrigação - Santos, Maurício Siqueira dos (2021)
The crescent imbalance between water demand and supply in agriculture, especially irrigated agriculture, has motivated the use of new irrigation management tools, including improving crop water requirement estimates, i.e., crop evapotranspiration (ETc). Improving the ETc implies adjusting the parameters used to estimate it, that is, the reference evapotranspiration (ETo) and the crop coefficients (Kc) throughout the crop cycle. Kc can be derived using crop parameters such as leaf area index (LAI), the fraction of ground cover (fc), and plant height since Kc represents a fraction of the ETo of any vegetation, under the conditions in which it is being cultivated. Thus, this work aimed to evaluate the yield responses of achenes and sunflower oil content submitted to different irrigation strategies and assess the effectiveness of the Allen e Pereira (2009) approach to derive the sunflower crop coefficients. The experiment was conducted inside a rainout shelter, in the 2019/20 growing season, in an experimental area of the Irriga System - UFSM. The experimental design was a completely randomized (DIC), organized in a 2x4 factorial model, with three replications. Factor A was composed of residues on the soil surface (with and without straw), while factor B consisted of irrigation management. Fixed irrigations of ± 15 mm were applied whenever the available soil water (ASW) reached 80, 70, 60, and 50% of the TAW (total available water). Soil water content was monitored with FDR sensors, up to 55 cm in depth. We combined plant parameters, such as LAI and plant height, with climate variables (relative humidity, wind speed) and the effects of density and the canopy transpiration resistance to estimate Kcb and Kc during the sunflower growing season, using the A&P approach. The Kcb derived for the initial, intermediate, and final phases were 0.25, 1.01, and 0.75, respectively. The association of the accumulated degree-days with the LAI throughout the cycle demonstrated an excellent adjustment, indicating that LAI can be estimated for sunflowers from air temperature. There was no interaction between straw and water management factors; different irrigation strategies did not result in statistical differences between yield and yield components. However, the oil contents decreased with the increasing of the total water depth during the cycle, indicating that the moment of occurrence of the deficit may have influenced this variable.